2019
DOI: 10.3390/app9102064
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Loose Zone of Roadway Surrounding Rock Using Wavelet Relevance Vector Machine

Abstract: By applying the Wavelet Relevance Vector Machine (WRVM) method, this research proposes the loose zone of roadway surrounding rock prediction. Based on the theory of relevance vector machine (RVM), the wavelet function is introduced to replace the original Gauss function as the model kernel function to form the WRVM. Five factors affecting the loose zone of roadway surrounding rock are selected as the model input, and the prediction model of the loose zone of roadway surrounding rock based on WRVM is establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Passive detection is based on the response of the sensor embedded in the structure or bonded on its surface without involving the actuation function. Often, piezoelectric sensors are used to directly measure structural acceleration, strain, and acoustic emission [33][34][35]. The active damage-detection technology uses an actuator to induce the stress wave signal, and a sensor to detect the travelling stress signal.…”
Section: Piezoelectric Transducers and Active Sensing Based On Piezoementioning
confidence: 99%
“…Passive detection is based on the response of the sensor embedded in the structure or bonded on its surface without involving the actuation function. Often, piezoelectric sensors are used to directly measure structural acceleration, strain, and acoustic emission [33][34][35]. The active damage-detection technology uses an actuator to induce the stress wave signal, and a sensor to detect the travelling stress signal.…”
Section: Piezoelectric Transducers and Active Sensing Based On Piezoementioning
confidence: 99%
“…Xue [20] combined the genetic algorithm (GA) and backpropagation (BP) neural network to analyze an 18 datasets database and found that the predictive performance of the new proposed GA-BP is much better than the original BP model. Liu et al [21] utilized a wavelet relevance vector machine in broken rock zone (BRZ) prediction, and the proposed model is showing a square correlation coefficient of 0.95.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility and reliability of the piezoelectric active sensing method, with respect to the monitoring of the shear failure of composite rocks, was therefore experimentally demonstrated in this study.Sensors 2020, 20, 1376 2 of 17 the damage, and issue timely warnings [6,7]. It is therefore necessary to conduct further research on the shear failure monitoring of composite rocks.At present, studies have been conducted with respect to the stability evaluation of rocks [8,9] and rock failure monitoring [10][11][12]. With respect to rock failure monitoring, there are four main methods:(1) the monitoring of micro-seismic signals to conduct a preliminary analysis of the rock failure characteristics [13,14]; (2) the monitoring of acoustic emission signals to investigate the characteristics and surface degradation of soft rock, in addition to the development of a roughness damage model based on the acoustic emission time characteristics [15]; (3) the use of acoustic waves for the evaluation of the rock mass characteristics in the damaged area of the rock slope excavation [16]; and (4) the use of fiber Bragg grating (FBG) sensors for the monitoring of the surrounding rock stability of tunnels [17].…”
mentioning
confidence: 99%
“…At present, studies have been conducted with respect to the stability evaluation of rocks [8,9] and rock failure monitoring [10][11][12]. With respect to rock failure monitoring, there are four main methods:…”
mentioning
confidence: 99%